PENGARUH IMPLEMENTASI GREEN ACCOUNTING, KEPEMILIKAN INSTITUSIONAL, DAN ENVIRONMENTAL DISCLOSURE, TERHADAP SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Jumadi Jumadi; Helmi Herawati; Nina Yulianasari (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to examine the effect of Green Accounting Implementation, Institutional Ownership, and Environmental Disclosure on Sustainable Development Goals (SDGs) in mining companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. The population of this study consists of 63 mining companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Data collection was conducted using purposive sampling, resulting in a sample of 8 companies. The data used are secondary data obtained from Annual Reports and Sustainability Reports published through the official website of the Indonesia Stock Exchange (IDX) at www.idx.com and the official websites of each company. The analytical method used in this research is multiple linear regression analysis. The results of this study indicate that Green Accounting implementation (X1) and Environmental Disclosure (X3) have no effect on Sustainable Development Goals (SDGs). Meanwhile, Institutional Ownership (X2) has a significant negative effect on Sustainable Development Goals (SDGs). The results of this study also show that Green Accounting implementation (X1), Institutional Ownership (X2), and Environmental Disclosure (X3) simultaneously have a significant effect on Sustainable Development Goals (SDGs). Keywords: Green Accounting, Good Corporate Governance (Gcg), Environmental Disclosure, Sustainable Development Goals (Sdgs), Mining Companies.